Vibrational Spectra and Gas-Phase Structure of N-Methyl-S,S-bis(trifluoromethyl)sulfimide, CH3NS(CF3)2 - Trautner, Frank (2005)
The molecular structure of N-methyl-S,S-bis(trifluoromethyl)sulfimide, CH3N=S(CF3)2, was determined by gas electron diffraction and quantum chemical calculations [B3LYP and MP2 with 6-31+G(2df,p) basis sets]. Furthermore, vibrational spectra, IR (gas) and Raman (liquid), were recorded. These spectra were assigned by comparison with analogous molecules and with calculated frequencies and intensities (HF, B3LYP, and MP2 with 6-311G* basis sets). All experimental data and computational methods result in a single conformer with syn orientation of the CH3 group relative to the bisector of the two CF3 groups. The molecule possesses C1 symmetry, slightly distorted from Cs symmetry. The N=S bond length in this compound [1.522(10) Å] is longer than that in imidosulfur difluorides RN=SF2 [1.476(4) Å - 1.487(5) Å].